Weight‐adjusted tinzaparin for the prevention of venous thromboembolism after bariatric surgery. (31st August 2018) - Tseng, E. K.; Kolesar, E.; Handa, P.; Douketis, J. D.; Anvari, M.; Tiboni, M.; Crowther, M. A.; Siegal, D. M.
Summary: Essentials The optimal dose and duration of thromboprophylaxis after bariatric surgery are unclear. We evaluated the safety of weight‐adjusted tinzaparin prophylaxis in 1212 patients. In‐hospital rates of venous thromboembolism and major bleeding were 0.2% and 1.8% respectively. In a sub‐set of patients, trough anti‐Xa levels did not show excessive anticoagulant activity. Summary: Background: Patients undergoing bariatric surgery are at moderate to high risk of venous thromboembolism (VTE). The optimal dose and duration of anticoagulant prophylaxis is uncertain. Objective: To evaluate the safety of extended‐duration weight‐adjusted tinzaparin after bariatric surgery. Patients/methods: We conducted a single‐center retrospective cohort study of consecutive patients undergoing bariatric surgery who received weight‐adjusted tinzaparin 4500–14 000 IU daily (75 IU kg −1 rounded to the nearest prefilled syringe) for 10 days after surgery (7–9 days post‐hospital discharge). Primary safety outcomes were the frequency of VTE and major bleeding within 30 days of surgery in patients receiving at least one dose of tinzaparin. Results: A total of 1279 patients undergoing bariatric surgery between July 2009 and December 2012 were reviewed, of whom 1212 received weight‐adjusted tinzaparin. Safety outcomes were collected for 819 patients at 30 days, and for 1212 patients in‐hospital only. The median age was 45.0 years, median weight was 130.0 kg and 98.8% of patients underwent gastric bypass or sleeve gastrectomy. In patients completing 30 days of follow‐up, VTE occurred in 4/819 (0.5%) and major bleeding occurred in 13/819 patients (1.6%). In‐hospital rates of VTE and major bleeding during surgical admission were 3/1212 (0.2%) and 22/1212 (1.8%), respectively. Conclusions: Extended thromboprophylaxis with weight‐adjusted tinzaparin appears to be a safe strategy after bariatric surgery, with low rates of postoperative VTE and major bleeding.